Turning Insight into Action: A Case Study Assessing the Use of Consumer Behavior Data in Minor League Baseball Marketing and Communication Strategies - Jessica R. Braunstein-Minkove; Ari Kim (Journal of Applied Sports Management, 2023)
As the usage of data-driven decision-making (DDDM) has increased in sport business operations, organizations must refine the ways in which they both obtain and use data to understand and, ideally, meet the needs of their consumers. A qualitative analysis, including eight in-depth interviews with a Minor League Baseball’s (MiLB) front office staff, was conducted. This was done in order to better understand the organization’s decision-making process and how they use various types of data, including the results of quantitative results from an academic study, when determining how best to reach their consumers. After a thematic analysis, three primary and six secondary themes were identified, including Use of Data Analytics (Strategic, Tactical), Application of Data Analytics (Confirmation, New Markets), and Data Sharing (Open Channels, Closed Channels). Practical and theoretical implications, as well as limitations and future research directions, are discussed.
Keywords: data-driven decision-making; strategic communication; consumer behavior; Minor League Baseball